Potential complexes of NaCF3SO3-tetraethylene dimethyl glycol ether (tetraglyme)-based electrolytes for sodium rechargeable battery application - Su, N.C.; Noor, Siti Aminah Mohd; Roslee, M.F.; Mohamed, Nor Sabirin; Ahmad, Azizan; Yahya, Muhd Zu Azhan (Springer Verlag (Germany), 2019)
The increasing energy demand on available global lithium resources has created concerns on development of new and advanced sustainable energy sources. Sodium-based batteries have emerged as promising substitutions to Li-based batteries. We describe here sodium trifluoromethanesulfonate (NaCF 3 SO 3 ) electrolyte system based on tetraethylene glycol dimethyl ether (tetraglyme). The ionic conductivity of the electrolytes showed a maximum value of 1.6 mS cm −1 for 40 mol% of NaCF 3 SO 3 at room temperature and increased up to of 9.5 mS cm −1 at 373 K. The system showed the anodic stability of the electrolytes up to ca. 5.2 V (Na + /Na) and facile deposition of sodium began at relatively low overpotential, around − 0.01 V vs. Na + /Na, which showed a good reversibility of the electrolytes. Preliminary tests of the electrolyte in half sodium-ion cells employing Na 3 V 2 (PO 4 ) 3 as cathode electrodes were performed and the cells delivered capacity of 74 mAh g −1 at C/10. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.